DEVELOPMENT OF ARTISTIC AND AESTHETIC ABILITIES IN STUDENTS THROUGH LITERATURE (Academicia Globe: Inderscience Research, 2023)
In this article talks about the extent to which students develop artistic and aesthetic abilities through children's literature, the formation in them of attention and worldview to literature and the images given in it, through which the knowledge of younger school-age students is developed.